China's COVID-19 Vaccine Diplomacy as China's Effort in Increasing Its Influence in the ASEAN Region - Sari, Venisa Yunita (Universitas Sebelas Maret, 2021)
The coronavirus outbreak (now known as COVID-19) is rapidly spreading throughout the world, and Southeast Asia is no exception. COVID-19 has affected many aspects of human life. The threat of this global pandemic is transnational, so regional and multilateral cooperation is needed. Therefore, it is necessary to find a vaccine to defeat the pandemic. Developed countries began to race to find vaccines and put the first access to vaccines for the benefit of their countries. In this case, China is a country that offers cooperation in providing massive vaccines to developing countries, including ASEAN member countries through its vaccine diplomacy scheme. This offer of cooperation cannot be separated from China's own interests. This research uses a qualitative case study method with analytical descriptive. This study uses an approach to China's interests and geopolitics in the Southeast Asia region. This article intends to explore and elaborate on China's efforts to increase its influence in the ASEAN region as a form of its geopolitical strategy in the form of vaccine diplomacy. The results of the research in this article are that China seeks to improve its image and achieve geopolitical interests in ASEAN by taking advantage of opportunities from the distribution of Sinovac and Sinopharm vaccines.